2009
DOI: 10.1149/1.3203966
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Material and Process Interactions on BEOL Integration

Abstract: In agreement with the ITRS roadmap, there have been several publications supporting the reduction in critical dimensions and the introduction of new materials to semiconductor processing (1,2,3). This paper highlights the observations and solutions to some of the critical material and process interactions encountered during the integration of the back end of line interconnect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Specifically, Goto et al, 393 and Liu et al, 394 have both observed UV cure induced hydrogen loss and more dramatic compressiveto-tensile (-250 MPa to 100 MPa) stress changes in PECVD SiCNH Cu cap materials. Even more dramatic -500 MPa to 750 MPa stress swings have been reported by Spooner et al 9 Liu also observed using FTIR that significant UV-induced structural modifications occurred for SiCNH Cu cap materials with higher nitrogen and hydrogen content. 394 Interestingly though, small (< 1-2%) changes in dielectric constant and film thickness for SiCNH and SiOCH Cu cap materials with UV curing were observed relative to pSiOCH materials.…”
Section: Vi2 Film Stress Engineeringmentioning
confidence: 68%
See 3 more Smart Citations
“…Specifically, Goto et al, 393 and Liu et al, 394 have both observed UV cure induced hydrogen loss and more dramatic compressiveto-tensile (-250 MPa to 100 MPa) stress changes in PECVD SiCNH Cu cap materials. Even more dramatic -500 MPa to 750 MPa stress swings have been reported by Spooner et al 9 Liu also observed using FTIR that significant UV-induced structural modifications occurred for SiCNH Cu cap materials with higher nitrogen and hydrogen content. 394 Interestingly though, small (< 1-2%) changes in dielectric constant and film thickness for SiCNH and SiOCH Cu cap materials with UV curing were observed relative to pSiOCH materials.…”
Section: Vi2 Film Stress Engineeringmentioning
confidence: 68%
“…7 One significant impact of this incidental exposure is UV-induced stress changes in the Cu cap layer, typically SiNH or SiCN, on which the pSiCOH film is deposited. 8,9 Since interconnects are composed of up to a dozen wiring layers, 6 the stress of each layer is additive and can subject the interconnect wiring levels to substantial stresses. In some cases, the tensile stress can become high enough to induce cracking in the pSiCOH film, especially when the wafer is subjected to additional stresses during the chip packaging process.…”
Section: Vi2 Film Stress Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, it has been determined that the dielectric constant of SiO 2 can be reduced by using doping with carbon-containing organics. ,, The resulting SiCOH materials have dielectric constants in the range from 2.7 to 3.0, and even lower values are possible by adding porosity. On the flip side, these new materials exhibit limited chemical stability, requiring special care during microelectronics manufacturing. , One of most difficult challenges when patterning the SiCOH dielectric is to minimize damage during the photoresist stripping processes, which typically relies on the use of plasmas with ions and radicals that can remove methyl groups from the surface of the SiCOH. , Because of this, the surface becomes hydrophilic, facilitating water absorption and leading to an increase in the dielectric constant of the material. ,, Several processes have been developed to minimize these problems, but those are multistep and introduce additional complications. , …”
Section: Introductionmentioning
confidence: 99%